Adverse events in the province of Tungurahua - Tamayo, Jorge (2017)
In the present investigation we analyze the main adverse events that occur most frequently in the province of Tungurahua such as volcanic activity, floods, landslides, explosions, forest and structural fires. Emergencies originate from natural disasters, produced by the same nature and anthropic caused by unconscious acts of people, causing human losses and irreparable environmental damage to the environment, at a particular site and at a given time. A comparative analysis is carried out between the years 2013 and 2017, which shows the evolution of the different catastrophic events registered in the Risk Management Secretariat. Converter. DOI: https://doi.org/10.31164/bcoyu.13.2017.632 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/632